The Architecture of Security in the Asia-Pacific - Huisken, Ron (Strategic and Defence Studies Centre (SDSC), 2009)
We cannot expect in East Asia over the foreseeable future to see the sort of conflation of sovereign states that has occurred in Europe. We must anticipate that, for the foreseeable future, the requirement will be for the sensible management and containment of competitive instincts.The establishment of a multilateral security body in East Asia that includes all the key players, and which the major powers invest with the authority to tackle the shaping of the regional security order, remains a critical piece of unfinished business.